TMS 2023 152nd annual meeting & exhibition : supplemental proceedings (Springer, 2023)
This collection presents papers from the 152nd Annual Meeting & Exhibition of The Minerals, Metals & Materials Society.
Includes indexes.
Keywords: Materials -- Congresses.; Materials -- Technological innovations -- Congresses.; elektronické knihy; electronic books